The Influence of Current Ratio, Net Profit Margin, Total Asset Turnover, And Debt to Equity Ratio on Share Prices in Manufacturing Companies in The Property and Real Estate Sector on The Indonesia Stock Exchange for the 2019-2021 Period - Natasya Fajriah; Hemima Franika Br Ginting; Herlin Munthe; Maduma Sari Sagala (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
Numerous industries provide investors with various funding options in today's rapidly evolving business and technology landscape. One particularly intriguing area in this regard is investment. Investment refers to allocating cash into various assets for a specific duration to generate profits, such as income or capital appreciation. Infrastructure development has led to the management of several industries, including property and real estate. Property can stimulate other economic sectors by providing employment opportunities and enhancing overall societal well-being. This is further bolstered by the rapid growth of the property sector, driven by the consistent availability of land and the rising public demand for housing and office spaces. Based on the data results, it is evident that there was an upsurge in demand for property and real estate in 2019. In contrast, production was sluggish expansion across all industries during the Covid-19 pandemic. Share prices will rise with increased demand and fall with less demand. This is evident in the company's effective management of shareholders. Financial reports are crucial for the company's future. Financial report data can be utilized as a decisive factor in decision-making. Investors can make informed investment decisions by evaluating the financial performance of PT. Alam Sutera Reality Tbk, PT. Bumi Serpong Tbk, and PT. Bekasi Fajar Industri Estate Tbk. This assessment can be done by calculating the liquid or illiquid ratio, which is determined by the company's Current Ratio, Net Profit Margin, Total Asset Turnover, and debt-to-equity ratio.